CORRECTION OF VITAMIN AND MINERAL STATE IN SCHOOLCHILDREN IN AUTUMN - S.V. Talashova (Вопросы современной педиатрии, 2009)
Despite the relatively simple pharmacology of vitamins, pediatricians have much questions and difficulties in administration of these drugs.The article gives an answer to the question of reasonability of vitamins and mineral complexes administration in autumn; and target groups of children, demanding additional correction of vitamin and mineral state of organism, are described. The article reflects the opinion of pharmacist on the criteria of choice of vitamin-mineral complex from the pharmaceutical and technological point of view.Key words: children, school age, vitamins.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(4):111-115)